Diagnostic Accuracy of Echocardiography in Assessment of Ejection Fraction Taking CT-Cardiac Function Analysis as Gold Standard - Ishtiaq, Bushra; Awan, Muhammad Wasim; Rashid, Uzma; Zahra, Shan E; Iqbal, Shaghaf; Mughal, Huma Mahmood (Biological and Clinical Sciences Research Journal, 2025)
Ejection fraction (EF) is a vital parameter in assessing cardiac function and guiding therapeutic decisions. While echocardiography remains the most commonly used modality due to its non-invasiveness and accessibility, its diagnostic accuracy in EF estimation has been debated. Cardiac computed tomography (CT), although less frequently utilized, offers potential advantages in EF evaluation. Objective: To determine the diagnostic accuracy of ejection fraction (EF) measurements obtained via echocardiography and to compare these results with those obtained from cardiac CT. Methods: This observational, comparative study was conducted at KRL Hospital, Islamabad, from December 15, 2024, to March 15, 2025. After obtaining ethical approval from the institutional review board, a total of 100 patients aged 20–70 years of both genders, presenting with suspected or known cardiac conditions requiring EF assessment, were recruited through non-probability consecutive sampling. EF was measured for all participants using both transthoracic echocardiography and cardiac CT. Sensitivity and specificity for detecting abnormal EF were calculated using CT findings as the reference standard. Statistical analysis was conducted using SPSS version 25. Results: Echocardiography demonstrated moderate diagnostic accuracy for EF assessment, with a sensitivity of 55% and specificity of 67%. In contrast, cardiac CT showed superior diagnostic performance, achieving a sensitivity of 74% and specificity of 80% in detecting abnormal EF. Conclusion: Echocardiography provides moderate diagnostic accuracy for evaluating ejection fraction, with relatively lower sensitivity and specificity compared to cardiac CT. The findings suggest that cardiac CT may serve as a more reliable modality for EF assessment, particularly in cases where precise evaluation is critical.